Development of Innovative Activity of University Teachers: Philosophical and Psychological Perspectives - Yu. N. Gut; L. E. Tursunov; M. V. Lanskikh; Sh. B. Akhmedova (Высшее образование в России)
In the era of the development of innovative technologies, the processes taking place in universities determine new requirements for the personality and professional competence of a teacher. A modern teacher is not just a transmitter of information and accumulated experience, but also a person who understands the essence of modern life and strives to harmoniously fit into existing realities, while focused on changing his consciousness, worldview and openness to everything new. In this connection, the problem of the teacher’s psychological readiness for innovation, as a component of his professionalism, is relevant. The purpose of the study: to study the peculiarities of readiness for innovation and identify the main barriers preventing the development of innovations among university teachers; based on the results obtained, to develop a methodology for the development of innovative activity of teachers. The study involved 156 university teachers aged 27 to 40 years with 1 to 15 years of work experience at the university. The study revealed that about a third of teachers show a low level of readiness for innovation. Only 22% of teachers have a high level of innovation activity. In the structure of readiness for innovation, they will have a motivational component, indicating a desire for success in achieving their goals. It was also found that the leading factors hindering the innovative activity of teachers are: insufficient awareness of possible innovative activities at the university; the belief that only the traditional education system is effective; lack of assistance in mastering innovations in the team, as well as fear of negative performance results. The systematization of the theoretical and empirical data obtained made it possible to develop a methodology for the development of innovative activity of university teachers, consisting of two main directions: environmental – features of the scientific and educational innovative environment; subjective – motivation, level of training and personal characteristics of teachers.